The Krakenes late-glacial palaeoenvironmental project - Birks, HH; Battarbee, RW; Beerling, DJ; Birks, HJB; Brooks, SJ; Duigan, CA; Gulliksen, S; Haflidason, H; Hauge, F; Jones, VJ; Jonsgard, B; Karevik, M; et al. (KLUWER ACADEMIC PUBL, 1996)
Krakenes is the site of a small lake on the west coast of Norway that contains a long sequence of late-glacial sediments. The Younger Dryas is well represented, as a cirque glacier developed in the catchment at this time. This site offers unique opportunities to reconstruct late-glacial environments from independent sources of evidence; physical evidence (glacial geomorphology, sedimentology, palaeomagnetism, radiocarbon dating), and biological evidence from the remains of animals and plants derived from both the terrestrial and aquatic ecosystems. This report describes the background to the site, and the international multidisciplinary project to reconstruct late-glacial and early Holocene environmental and climatic changes at Krakenes.